A Conserved Di-Basic Motif of Drosophila Crumbs Contributes to Efficient ER Export. - Kumichel, A.; Kapp, K.; Knust, E. (Traffic, 2015)
The Drosophila type I transmembrane protein Crumbs is an apical determinant required for the maintenance of apico-basal epithelial cell polarity. The level of Crumbs at the plasma membrane is crucial, but how it is regulated is poorly understood. In a genetic screen for regulators of Crumbs protein trafficking we identified Sar1, the core component of the coat protein complex II transport vesicles. sar1 mutant embryos show a reduced plasma membrane localization of Crumbs, a defect similar to that observed in haunted and ghost mutant embryos, which lack Sec23 and Sec24CD, respectively. By pulse-chase assays in Drosophila Schneider cells and analysis of protein transport kinetics based on Endoglycosidase H resistance we identified an RNKR motif in Crumbs, which contributes to efficient ER export. The motif identified fits the highly conserved di-basic RxKR motif and mediates interaction with Sar1. The RNKR motif is also required for plasma membrane delivery of transgene-encoded Crumbs in epithelial cells of Drosophila embryos. Our data are the first to show that a di-basic motif acts as a signal for ER exit of a type I plasma membrane protein in a metazoan organism.